Improving the Accuracy of Small and Medium Enterprise Sales Predictions in Deli Serdang Regency by Implementing Business Intelligence Using the Decision Tree Algorithm - M Dico Triyadi; Darmeli Nasution (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study focuses on improving the accuracy of sales prediction in Small and Medium Enterprises in Deli Serdang Regency through the application of Business Intelligence (BI). By using the Decision Tree algorithm, a prediction model is built based on historical sales data, seasonal factors, and macroeconomic variables. The evaluation results show that the developed model is able to predict sales with the right accuracy. In addition, this model also successfully identifies key factors that influence sales, such as price, promotion, and economic conditions. This study concludes that the application of BI can be an effective tool for Small and Medium Enterprises in making better decisions and increasing competitiveness.